Growing together as teacher researchers - Pineda Báez, Clelia; Clavijo Olarte, Amparo (Colombian Applied Linguistics Journal, 2003)
This article focuses on the description of an innovative academic program implemented in the Masters Program in Applied Linguistics to TEFL at Distrital University in Bogotá, Colombia that aimed at facilitating EFL teachers’ undertaking of research in schools in Bogotá. The process of working collaboratively included identifying teachers’ feelings related to their research capabilities. The program allowed students to develop awarenessof the applications of qualitative research in education. This experience contributed to bridging the gap between reflective practice and research practices. It also promoted a high quality of academic debate.